PENGARUH MODEL PEMBELAJARAN TWO STAY TWO STRAY TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN IPAS KELAS IV SEKOLAH DASAR - Heppy Ester Sitanggang; Darinda Sofia Tanjung; Patri Janson Silaban; Bogor Lumbanraja; Risiki Bastanta B. Manalu (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2026)
This study aims to determine whether there is an effect of the Two Stay Two Stray learning model on students' learning outcomes in the fourth-grade IPAS subject, "Aku dan Kebutuhanku" (Me and My Needs). The research method used is an experimental method with a quantitative research design. Total sampling technique was used for sample selection. The research design employed was a one-group pretest-posttest design. The success rate of students' learning outcomes increased, as evidenced by the calculation of the correlation coefficient, where the calculated r-value (0.626) was greater than or equal to the table r-value (0.349). Furthermore, hypothesis testing compared the calculated t-value to the table t-value. The calculated t-value was 4.395, while the table t-value was 1.693. Because the calculated t-value was greater than or equal to the table t-value (4.395 ≥ 1.693), the alternative hypothesis (Ha) was accepted, and the null hypothesis (Ho) was rejected. This indicates that there is a significant effect of the Two Stay Two Stray learning model on students' learning outcomes in the fourth-grade IPAS class.